Angiotensin converting enzyme 2: A new important player in the regulation of glycemia - Chhabra, Kavaljit H. (IUBMB Life, 2013)
In spite of the novel anti-diabetic drugs available on the market, type 2 diabetes mellitus (T2DM) affects nearly 25 million people in the USA and causes about 5% of all deaths globally each year. Given the rate and proportion by which T2DM is affecting human beings, it is indispensable to identify new therapeutic targets that can control the disease. Recent pre-clinical and clinical studies suggest that attenuating the activity of the renin-angiotensin system (RAS) could improve glycemia in diabetic patients. Angiotensin converting enzyme 2 (ACE2) counteracts RAS over-activity by degrading Ang-II, a vasoconstrictor, to Ang-(1-7) which is a vasodilator. A decrease in ACE2 and an increase in ADAM17-mediated shedding activity have been observed with the progression of T2DM suggesting the importance of this mechanism in the disease. Indeed, restoration of ACE2 improves glycemia in db/db and Ang-II-infused mice. The beneficial effects of ACE2 can be attributed to reduced oxidative stress and ADAM17 expression in the islets of Langerhans in addition to the improvement of blood flow to the β-cells. The advantage of ACE2 over other RAS blockers is that ACE2 not only counteracts the negative effects of Ang-II but also increases Ang-(1-7)/MasR [a receptor through which Ang-(1-7) produces its actions] signaling in the cells. Increased Ang-(1-7)/MasR signaling has been reported to improve insulin sensitivity and glycemia in diabetic animals. Altogether, ACE2/Ang-(1-7)/MasR axis of the RAS appears to be protective in T2DM and strategies to restore ACE2 levels in the disease seem to be a promising therapy for Ang-II-mediated T2DM.